2017
DOI: 10.1073/pnas.1620400114
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein dynamics before aggregation

Abstract: Prion diseases, like Alzheimer's disease and Parkinson disease, are rapidly progressive neurodegenerative disorders caused by misfolding followed by aggregation and accumulation of protein deposits in neuronal cells. Here we measure intramolecular polypeptide backbone reconfiguration as a way to understand the molecular basis of prion aggregation. Our hypothesis is that when reconfiguration is either much faster or much slower than bimolecular diffusion, biomolecular association is not stable, but as the recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…Earlier studies have indicated that the dynamics in the U state of prion protein play a role in initiating misfolding and oligomerisation (Yu et al, 2012; Srivastava and Lapidus, 2017). In the current study it was shown that the fluctuations within the N state of the protein are responsible for the misfolding of the moPrP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have indicated that the dynamics in the U state of prion protein play a role in initiating misfolding and oligomerisation (Yu et al, 2012; Srivastava and Lapidus, 2017). In the current study it was shown that the fluctuations within the N state of the protein are responsible for the misfolding of the moPrP.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, unlike the protein used in the current study, the protein used for the force spectroscopy measurements had a disrupted disulphide bond, and it is known that disruption of the disulphide bond in the prion protein leads to its unfolding to a molten globule form (Maiti and Surewicz, 2001; Honda, 2018). Fluctuations in SHaPrP (90-231), which could be important in aggregation, had also been identified using Trp-Cys contact quenching experiments carried out at pH 4.4 (Srivastava and Lapidus, 2017). In that study, the data appeared to suggest that the fluctuations might arise from the U state, but that could not have been the case because several other studies have shown that SHaPrP (90-231) is natively structured at acidic pH (Bjorndahl et al, 2011; Donne et al, 1997), including at pH 4 (Khan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A high load of energy is required for the activity of the proton pump to maintain the acidic conditions required for the activity of lysosomal enzymes (Mindell, 2012). A low pH could serve as a spark triggering protein aggregation as it was shown for prion conversion (DeMarco and Daggett, 2007;Srivastava and Lapidus, 2017). Indeed, a protonation-based model approach demonstrated that the partial unfolding and dissociation of one alpha-helices of PrP C result in the loss of critical longrange salt bridges, which favor the conversion to a PrP Sc -like structure (DeMarco and Daggett, 2007).…”
Section: Protein Aggregation Within Lysosomesmentioning
confidence: 99%
“…These data indicate that the presence of these ions could have a great effect on both the water mobility in the solvation shell and protein mobility in vitro. The rate of dimerisation is directly linked to the rate of protein reconfiguration, where slow reconfiguration allows for dimerisation to occur, while fast reconfiguration reduces the likelihood of sustainable contacts that result in successful dimerisation 17 . The mobility of water increases in bulk and in the solvation shell in the presence of CsI compared to…”
Section: Csi But Reduced In the Presence Of Naclmentioning
confidence: 99%